Prevalence of Sleep Disordered Breathing in Children With Myelomeningocele. Issue 4 (28th December 2020) - Rocque, Brandon G; Maddox, Mary Halsey; Hopson, Betsy D; Shamblin, Isaac C; Aban, Inmaculada; Arynchyna, Anastasia A; Blount, Jeffrey P
Abstract: BACKGROUND: Retrospective studies have shown high rates of sleep disordered breathing in children with myelomeningocele. However, most patients included in those studies underwent polysomnography because of symptoms, so the prevalence of sleep disordered breathing in this population is unknown. OBJECTIVE: To determine the prevalence of sleep disordered breathing in children with myelomeningocele using screening polysomnography. METHODS: In this cross-sectional study, all children with myelomeningocele seen in a multi-disciplinary spina bifida clinic between 2016 and 2020 were referred for polysomnography regardless of clinical symptoms. Included children had not previously undergone polysomnography. The primary outcome for this study was presence of sleep disordered breathing, defined as Apnea-Hypopnea Index (AHI, number of apnea or hypopnea events per hour of sleep) greater than 2.5. Clinical and demographic variables relevant to myelomeningocele were also prospectively collected and tested for association with presence of sleep apnea. RESULTS: A total of 117 participants underwent polysomnography (age 1 mo to 21 yr, 49% male). The majority were white, non-Hispanic. Median AHI was 1.9 (interquartile range 0.6-4.2). A total of 49 children had AHI 2.5 or greater, yielding a sleep disordered breathing prevalence of 42% (95% CI 33%-51%). In multivariable logistic regression analysis, children with more rostral neurological lesion levels had higher odds of sleep disordered breathing (OR for thoracic, mid-lumbar, and low-lumbar: 7.34, 3.70, 4.04, respectively, compared to sacral level, P  = .043). CONCLUSION: Over 40% of a sample of children with myelomeningocele, who underwent screening polysomnography, had significant sleep disordered breathing. Routine screening polysomnography may be indicated in this population.